2023
DOI: 10.3892/etm.2023.11911
|View full text |Cite
|
Sign up to set email alerts
|

Increased ENT2 expression and its association with altered purine metabolism in cell lines derived from different stages of colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most prevalent malignant cancer types worldwide. Although the purine metabolism pathway is vital for cancer cell survival, little is known about the role of equilibrative nucleoside transporter 2 (ENT2) in CRC development and its association with purine metabolites. The aim of the present study was to evaluate the levels of hypoxanthine phosphoribosyl transferase (HPRT), hypoxanthine and uric acid (UA), as well as xanthine oxidase (XO) activity, and investigate their assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Consistent with these data, high levels of hypoxanthine were recently identified as biomarker in human melanoma metastasis 31 , lung squamous cell carcinoma metastasis 32 and prostate cancer aggressiveness 33 . Similarly, the highest level of hypoxanthine was reported in stage IV compared to stage II and III, indicating its role in colorectal cancer progression 34 . These reports may further support the role of hypoxanthine in cancer metastasis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with these data, high levels of hypoxanthine were recently identified as biomarker in human melanoma metastasis 31 , lung squamous cell carcinoma metastasis 32 and prostate cancer aggressiveness 33 . Similarly, the highest level of hypoxanthine was reported in stage IV compared to stage II and III, indicating its role in colorectal cancer progression 34 . These reports may further support the role of hypoxanthine in cancer metastasis.…”
Section: Discussionmentioning
confidence: 94%
“…During the purine catabolism pathway, hypoxanthine is converted to xanthine, which is then converted to uric acid by xanthine oxidase (XOR). This is associated with the production of ROS as by-product 34 . It has been demonstrated that the loss of XOR expression is associated with aggressiveness in breast cancer 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of SLC29A2 , also known as ENT2 , suggests its importance in facilitating hypoxanthine transport, which is necessary for enhanced DNA synthesis through hypoxanthine recycling. In conclusion, ENT2 shows potential as a target for developing therapeutics (Naes et al, 2023 ). Elevated levels of ENT2 in the blasts at the time of diagnosis of AML were associated with a lower response to induction therapy (Rodríguez-Macías et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…As tissue biopsy is invasive and relatively difficult, we chose human CRC cell lines as the subject of our study. CRC cell lines were classified based on Dukes’ classification criteria by ATCC and previous studies [ 15 , 23 ]. The Dukes’ staging system classifies CRC into four groups known as Dukes’ A, B, C, and D groups, which represent stages I, II, III, and IV of CRC.…”
Section: Discussionmentioning
confidence: 99%